Melt quality induced failure of electrical conductor (EC) grade aluminum wires - Khaliq A.; Rafiq M.A.; Ali H.T.; Ahmed F.; Mehmood S.; Grandfielde J.; Ranjha S.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The failure of electrical conductor grade (EC) aluminum during wire drawing process was investigated. The fractured aluminum wires were subjected to Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray (EDX) analyses for an initial examination. Thermodynamic analyses of molten aluminum interaction with refractories was also carried out using FactSage at 710°C to predict the stable phases. The SEM/EDX analyses has revealed the inclusions in aluminum matrix. The typical inclusions observed were Al2O3, Al3C4 (Al-Carbide) and oxides of refractories elements (Al, Mg, Si and O) that have particle size ranging up to 5 μm. The transition metal boride particles were not identified during SEM/EDX analyses these might be too fine to be detected with this microscope. The overall investigation suggested that the possible cause of this failure is second phase particles presence as inclusions in the aluminum matrix, and this was associated with the poor quality of melt. During wire drawing process, these inclusions were pulled out of the aluminum matrix by the wiredrawing forces to produce micro-voids which led to ductile tearing and final fracture of wires. It was recommended to use ceramic foam filters to segregate inclusions from molten aluminum.